DISASTER VICTIM IDENTIFICATION – ARE WE PREPARED? Disaster Victim Identification - Hussain, Safdar; Hafeez, Noureen; Munawar, Anjum Zia; Khalil, Inayatur Rehman (Pakistan Armed Forces Medical Journal, 2006)
INTRODUCTIONDisasters, whether natural or man-inflicted, are unfortunately a fact of life. Mass casualties are encountered in a number of situations like collapse of buildings, crash of passenger airplanes, ship wrecks, train accidents, fires and explosions, war casualties, or even ethnic cleansing practices such as seen recently in Bosnia and Rwanda [1-3]. Acts of sabotage and crime may also produce mass casualties. Besides, the Mother Nature is also no less behind and often huge number of casualties are left behind in earthquakes, floods, tsunami, and volcanic eruptions. Unfortunately no one can predict when such a calamity might strike and the scale of its destruction.A mass disaster causes injury, death, or property damage on a scale that may affect from as low as a dozen of people to as much as encountered in the earthquake of 8 October 2005 in Pakistan; this catastrophe left behind more than 80,000 dead, thousands injured, and many still missing. A commonly accepted definition of mass disaster is “the death of more than 12 victims in a single event” [4]. In most countries a Mass Casualty Plan is to be implemented in the event of any mass disaster. Besides rescue and relief efforts, identification of the dead victims is one of the most important jobs in disaster management. The recovered human bodies may range from being relatively fresh and intact to highly degraded or decomposed. However, whatever the nature of the disaster, the public authorities have the basic responsibility for identifying the human remains [5, 6]. Generally, these plans cover medical services and other rehabilitation components.  Unfortunately provisions for the dead are often completely ignored in these plans in the developing countries. Generally, no thought is given as to how several hundred corpses would be found, accommodated, examined, and identified in a mass disaster. Therefore, in the context of identification, it is essential that every responsible public authority, forensic institute, and individual pathologist should make some forward provision for such an eventuality. In the wake of recent disasters, now the disaster victim identification (DVI) has emerged as a separate discipline. This article intends to review the contemporary methods and strategies for the disaster victim identification and to provide general guideline to develop any disaster victim identification (DVI) plans in Pakistan.